Mechanization In Learning English Language: A Learners’ Perception (Journal of Namibian Studies : History Politics Culture, 2024)
The current study aims to understand the attitudes of Indian multilingual undergraduate students toward the use of technology in English language learning. To make things easier, this investigation was divided into - a) the benefits of using these (technological aspects) and b) the purpose for which students use it, as well as c) their preference for it, in order to strengthen outcomes and determine whether it was beneficial to them or not. It is based on Richard Mayer's Multimedia Learning Theory (MMLT) 1997. A Concurrent Triangular MMR research approach was used. Empirical data was gathered using a questionnaire specially designed for this purpose, which included three sections- demographic data; technological proficiency; attitudes toward technology in English language learning. The findings of the study suggest that the use of technology in English language learning is advantageous for Indian multilingual undergraduate students.